The consideration of governance component for ICT services quality (ICTSQ) in Higher Education Institutions (HEIs) context - Nor, Rozi Nor Haizan; Alias, Rose Alinda; Abdul Rahman, Azizah (2012)
Today's dynamic development trend and competitive ICT era have seen drastic dependence on ICT usage and services. It drives organization towards improving the performance of its ICT services (ICTS). This is achievable by focusing on the organization's ICT mission and vision which depends on seamless coordination, effective monitoring and continuous action that only accessible through consistent governance of ICTS. It is important for the ICT services quality (ICTSQ) and achieving business aim and objectives. However, nowadays, most firms' governance process is ad-hoc and informal, no enterprise wide consistency and accountability weakness without formal approach to govern the complexity of ICTS. To address this issue, the study tries to reveal the governance components to be considered for ICTSQ by focusing on Higher Education Institutions (HEIs) since ICT and their services play an important role in the context of universities. Besides focusing on universities' core activities of teaching and learning, it also promotes technology development of the country. ICTS requires the governance component to ensure feasible and orderly function of planning, implementation, coordination and monitoring. Some previous general governance framework and IT governance developed by various organizations such as International Organization for Standardization (ISO), IT Infrastructure Library (lTIL) and Control Objectives for Information and related Technology (COB IT) have been reviewed, Hence, the reviews outcome and preliminary interviews are fundamental in understanding the governance of ICT services in the listing of governance component appropriate for ICTSQ within HEIs context. Ideas and guidelines from the findings should be useable for the relevant parties' assesment, measurement and improvement of their ICTSQ